Prevention of C. A. D. in India: A Novel Approach - Krishnamani, N. C. (New Frontiers in Medicine and Medical Research Vol. 11, 2021)
Coronary artery disease is the leading cause of death world over and main substrate is atherosclerosis. Conventional and newer risk factors fail to explain the advent of the disease in majority. A few representative case studies are presented who have suffered major coronary event and are devoid of the risk factors. Personal histories of these cases have been analysed and very important and interesting facts derived and a novel hypothesis has been proposed. Understanding them and implicating would have an immense affect on the prevention of this pandemic of coronary artery disease in our society.